(untitled) (Jurnal Simki Economic, 2024)
Economic growth is the increase in the production level of an economy measured through national income, including components such as government expenditure, exports, foreign direct investment, labor force, and inflation reflected in the Gross Domestic Product (GDP). This research analyzes the influence of these components on economic growth in 8 ASEAN countries during the period 2008-2021 using the Generalized Method of Moment (GMM) analysis method on dynamic panel data. With Stata 14 processing, the results of this study indicate that (1) government expenditure does not significantly affect economic growth, (2) exports have a positive and significant impact on economic growth, (3) foreign direct investment has a positive and significant impact on economic growth, (4) the labor force does not significantly affect economic growth, (5) inflation does not significantly affect economic growth.